Theoretical approach to the concept of sociometry and its benefits for the social sciences - Cano, Carlos Alberto Gómez; Páez , Claudia Cristian Ortiz; Delgado, Marcia Hernández (AWARI, 2023)
Sociometry allows researchers to quantify social relationships' preferences, choices, and rejections, facilitating an in-depth understanding of social structure and group cohesion. The study aimed to analyze the relevance and applicability of sociometrics for social research. A qualitative literature review research was conducted using a rigorous process of selecting documents in the Scopus database. This article comprehensively reviews sociometrics, a methodological and theoretical tool developed to measure interpersonal relationships and dynamics within groups and communities. The benefits of applying sociometric analysis in various fields, such as social psychology, education, social work, and community organization, were discussed. In addition, methodological and ethical challenges inherent in using sociometrics are addressed, and future directions for research are suggested. Sociometry has important relevance as a powerful tool for analyzing social networks, improving group dynamics, and designing more inclusive and functional environments.